Gambaran Kadar Asam Urat pada Lansia di Desa Pinabetengan Selatan Kecamatan Tompaso Barat - Jeane Leidi Ireine Sumarauw; Grace Marentek; Shearviano Shefa Mandagi (Jurnal Ilmiah Kesehatan, 2025)
Uric acid is the final metabolic product of purine, a component of nucleic acids found in the nucleus of body cells. Increased uric acid levels are influenced by several factors, one of which is age. Uric acid levels increase by a ratio of 3:1 in seniors over 60 years of age. Elderly individuals are at the final stage of their life and experience various physical, psychosocial, and spiritual changes, especially in those over 60 years of age. Therefore, monitoring uric acid levels in the elderly is very important to prevent various complications, especially gout which can worsen the quality of life of the elderly. The purpose of this study was to determine the profile of uric acid levels in the elderly in Pinabetengan Selatan Village. The research design was descriptive and observational. The population consisted of elderly people who agreed to undergo uric acid level testing between June and July 2025. A total of 55 individuals were selected using purposive sampling. Data were collected through laboratory observation, and processed through editing, coding, and tabulation. The results of the study on 55 respondents showed that 38 respondents (69%) experienced increased hiperurisemia, and 17 respondents (31%) had normal uric acid levels or hiperurisemia. The conclusion based on research data is that almost all elderly people in Pinabetengan Selatan Village, Tompaso Barat District who underwent uric acid level examination experienced increased uric acid levels.